Nemzetiségek törekvések kartográfiai ábrázolása cseh és szlovák példák alapján - Suba, János (Közép-Európai Közlemények, 2009)
The minorities of the AH Monarchy, aspiring to independent national statehood, had been planning their secession from Hungary since many decades. During the First World War they got the chance to dismember the Hungarian state not only on maps, but also in the reality. In case of fulfilling of the Romanian, Czech-Slovak and Yugoslav claims it would have remained only a stump of Hungary, which the successor states would readily divide among themselves, too. From a period of 1842–1919, we know 23 (!) different plans to alter the Hungarian borders. The paper presents the conceptions devised by Czech borders of the new Czech-Slovak state.